2018
DOI: 10.3390/nano8100782
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Tumor-Imaging Using a Thermo-Responsive Molecule with an Emissive Aminoquinoline Derivative

Abstract: We synthesized (2,4-trifluoromethyl-7-N-bis(2,5,8,11-tetraoxatridecane-13-yl)-aminoquinoline) TFMAQ-diEg4, an emissive aminoquinoline derivative that incorporated two tetraethyleneglycol chains into an amino group. TFMAQ-diEg4 showed fluorescence and thermo-responsive properties accompanied by a lower critical solution temperature (LCST), due to the introduction of the oligoethylene glycol chain. This thermo-responsive LCST behavior occurred at the border of a cloud point. Below and above the cloud point, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To achieve this, the fluorescence changes in various fluorophores were observed (Scheme (c)). We selected TFMAQ-diHEG , TFMAQ-diMe , and 15Nap-Cl as the fluorophores because these fluorophores show medium fluorescence intensities in polar solvents. Furthermore, these fluorophores possess different water solubilities and fluorescence quantum yields (Scheme and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this, the fluorescence changes in various fluorophores were observed (Scheme (c)). We selected TFMAQ-diHEG , TFMAQ-diMe , and 15Nap-Cl as the fluorophores because these fluorophores show medium fluorescence intensities in polar solvents. Furthermore, these fluorophores possess different water solubilities and fluorescence quantum yields (Scheme and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly in the field of tissue engineering and regenerative medicine, thermoresponsive PNIPAAm exposed immense potential, as it enabled the creation and harvest of biologically functional products called “cell sheets” through the control of the dynamic environment for cells upon a change in temperature [ 21 ]. Hence, it has important applications for thermoresponsive polymers as cancer cell culture platforms, such as fluorescence tumor imaging [ 22 ], drug delivery in tumor screening and anti-cancer treatment [ 23 ]. PNIPAAm-based scaffolds as in vitro tumor culture models have good application in the previous reported, which encapsulate cells in physically cross-linked viscoelastic scaffolds at body temperature and easily release the cells by cooling to room temperature [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported that TFMAQ exhibited fluorescence colour changes depending on solvent polarity and crystalline phase transition. The TFMAQ chromophore was further applied to thermo-responsive nanomaterials as in vivo tumour-imaging agent 23,24 . The TFMAQs were also derivatized to phenyl aromatic-substituted amine analogues to investigate the photophysical properties at solid state 25,26 .…”
Section: Introductionmentioning
confidence: 99%